Memprediksi Niat Beli Siswa pada Berbagi Aplikasi Seluler Ekonomis; Kajian Empiris saat New Normal - Muhammad Ashoer (Faculty of Economics and Business, Jenderal Soedirman University, 2022)
This study aims to investigate how essential product quality, service quality, discounts, and perceived ease of use that influence students’ intention in using sharing economy (SE) application during pandemic period. An online survey was conducted by directly scattering e-questionnaires link generated from google formulir to collect primary data from active students in Makassar, Indonesia. We selected 132 respondents (Grab users) who have met the judgment sampling and.then analyzed the collected primary data with structural equation modeling (SEM) and partial least squares (PLS). The result demonstrated that there was positive and significant relationship between service quality, discounts, perceived ease of use and purchase intention. Meanwhile, product quality were found to be not significant in predicting students’ behavior. Practically, the Grabs’ management should reconfirm and reassure the product quality that the vendor offers via their apps to stimulate users’s buying especially in the Covid-19 crisis. Theoritically, some potential constructs needs to revisit to enrich the current SE studies.